2021
DOI: 10.1155/2021/9133464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical, Functional, Spectral, and Thermal Characteristics of Sargassum wightii and Ulva rigida from Indian Coast

Abstract: Usage of seaweeds as a functional food/food ingredient is very limited due to paucity of scientific information about variations in the nutritional composition of seaweeds under diverse climatic conditions. Sargassum wightii and Ulva rigida seaweeds are found abundantly on the Southern Indian coastline and were thoroughly evaluated in this work. Crude fiber and lipid of S. wightii were higher (24.93 ± 0.23% and 3.09 ± 0.41%, respectively) as compared to U. rigida; however, U. rigida had higher crude protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
(83 reference statements)
1
6
1
Order By: Relevance
“…The value is higher compared with that of Rosemary et al (2019) in G. edulis (8.66 mL/g) and Udayangani, Wijesekara, and Wickramasinghe (2019) in U. lactuca (1 mL/g). The results of WHC of this study are lower than the observed values of Sakthivel and Devi (2015) in G. edulis (9.97 g/g), Wong and Cheung (2000) in U. lactuca (9.71 g/ g), Yaich et al (2011) in U. lactuca (6.66 g/g), and Kumar et al (2021) in U. rigida yet higher compared with those from studies by Rosemary et al (2019) in G. edulis (4.09 g/g). The significantly (p , 0.05) higher SWC and WHC values of dried seaweeds reflect that both U. lactuca and G. edulis can be used as texturizing and bulking agents in making low-calorie food products.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The value is higher compared with that of Rosemary et al (2019) in G. edulis (8.66 mL/g) and Udayangani, Wijesekara, and Wickramasinghe (2019) in U. lactuca (1 mL/g). The results of WHC of this study are lower than the observed values of Sakthivel and Devi (2015) in G. edulis (9.97 g/g), Wong and Cheung (2000) in U. lactuca (9.71 g/ g), Yaich et al (2011) in U. lactuca (6.66 g/g), and Kumar et al (2021) in U. rigida yet higher compared with those from studies by Rosemary et al (2019) in G. edulis (4.09 g/g). The significantly (p , 0.05) higher SWC and WHC values of dried seaweeds reflect that both U. lactuca and G. edulis can be used as texturizing and bulking agents in making low-calorie food products.…”
Section: Discussioncontrasting
confidence: 92%
“…Furthermore, hydrophilic nature, overall charge density, and particle size also play a role in defining the technofunctional properties of U. lactuca and G. edulis . In this study, SWC of U. lactuca ranged between 12.83 and 19.75 mL/g and of G. edulis ranged from 16.65 to 18.08 mL/g, and the results are in accordance with those of Sakthivel and Devi (2015) in G. edulis (20 mL/g), Wong and Cheung (2000) in U. lactuca (13 mL/g), and Kumar et al . (2021) in U. rigida (19.42 mL/g).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…S. wightii is a good source of nutrients like crude protein, crude fibre calcium, iron, and sulphur, etc. Moreover, water and oil holding capacity of S. wightii is directly related to its protein, fibre, and flavonoid contents that increase its antioxidant potential and provide a genuine reason to use it as a fibre rich ingredient in food products and nutraceuticals (Kumar et al, 2021). For health benefits, S. wightii can be infused for better flavour in coffee-based beverages (Kumar et al, 2019) and as a spice in the diet to improve the taste and nutritive value of food (Sumayaa and Kavitha, 2015).…”
Section: Role Of S Wightii In Aquaculturementioning
confidence: 99%
“…In this context, Sagar et al [1] described and gave new data on physicochemical and thermal characteristics of onion skin from fifteen Indian cultivars for possible food applications. Another example given by Kumar et al [2] evaluated the chemical, functional, spectral, and thermal characteristics of Sargassum wightii and Ulva rigida from the Indian Coast.…”
mentioning
confidence: 99%